3⋅a⋅b⋅a=b⋅a⋅a

Move a.

3⋅(a⋅a)⋅b=b⋅a⋅a

Multiply a by a.

3⋅a2⋅b=b⋅a⋅a

3a2b=b⋅a⋅a

Move a.

3a2b=b⋅(a⋅a)

Multiply a by a.

3a2b=b⋅a2

3a2b=ba2

Subtract ba2 from both sides of the equation.

3a2b-ba2=0

Subtract ba2 from 3a2b.

Move b.

3a2b-1a2b=0

Subtract a2b from 3a2b.

2a2b=0

2a2b=0

2a2b=0

Divide each term in 2a2b=0 by 2b.

2a2b2b=02b

Simplify 2a2b2b.

Cancel the common factor of 2.

Cancel the common factor.

2a2b2b=02b

Rewrite the expression.

a2bb=02b

a2bb=02b

Cancel the common factor of b.

Cancel the common factor.

a2bb=02b

Divide a2 by 1.

a2=02b

a2=02b

a2=02b

Simplify 02b.

Cancel the common factor of 0 and 2.

Factor 2 out of 0.

a2=2(0)2b

Cancel the common factors.

Factor 2 out of 2b.

a2=2(0)2(b)

Cancel the common factor.

a2=2⋅02b

Rewrite the expression.

a2=0b

a2=0b

a2=0b

Divide 0 by b.

a2=0

a2=0

a2=0

Take the square root of both sides of the equation to eliminate the exponent on the left side.

a=±0

Simplify the right side of the equation.

Rewrite 0 as 02.

a=±02

Pull terms out from under the radical, assuming positive real numbers.

a=±0

a=±0

±0 is equal to 0.

a=0

a=0

Solve for a 3*a*b*a=b*a*a